Karyotype analysis of the acute fibrosarcoma from chickens infected with subgroup J avian leukosis virus associated with v-src oncogene. Issue 2 (3rd March 2016) - Dong, Xuan; Ju, Sidi; Chen, Junxia; Meng, Fanfeng; Sun, Peng; Li, Yang; Wang, Xin; Wang, Yixin; Liu, Juan; Chang, Shuang; Zhao, Peng; Cui, Zhizhong
ABSTRACT: To understand the cytogenetic characteristics of acute fibrosarcoma in chickens infected with the subgroup J avian leukosis virus associated with the v- src oncogene, we performed a karyotype analysis of fibrosarcoma cell cultures. Twenty-nine of 50 qualified cell culture spreads demonstrated polyploidy of some macrochromosomes, 21 of which were trisomic for chromosome 7, and others were trisomic for chromosomes 3, 4, 5 (sex chromosome w), and 10. In addition, one of them was trisomic for both chromosome 7 and the sex chromosome 5 (w). In contrast, no aneuploidy was found for 10 macrochromosomes of 12 spreads of normal chicken embryo fibroblast cells, although aneuploidy for some microchromosomes was demonstrated in five of the 12 spreads. The cytogenetic mosaicism or polymorphism of the aneuploidy in the acute fibrosarcoma described in this study suggests that the analysed cells are polyclonal.